Control of pH Level Using Fuzzy Controller - Mohd Noor, Ilanur Muhaini (2009)
The idea of constructing this project is to simulate the control system of pH level by adding acid or base (alkali) into a process tank in a wastewater system to maintain the pH level to neutral value, which is pH 7. Environment has been ruined by lots of development especially at the industrial area. For that reason, it is important that the wastage is been taking care of as a preventative measure before things get worse. The control system of pH level in this project is done by using LabVIEW which is graphical programming environment software with the addition of fuzzy logic controller of MATLAB. Block diagram of the whole system is constructed in LabVIEW and the calculation of the amount of acid and alkali to be added to the process tank to maintain its pH level at neutral (pH = 7) is done by fuzzy logic controller. Control of pH in mix tank depends on the flow rate which could be manually control by several valves which enable either acid or base to be pumped in. The control development has been designed in LabVIEW block diagram and the Graphical User Interface (GUI) has been created in the LabVIEW front panel. The result of experiment could be easily controlled and several results could be compared to obtain the best neutralization system. Further use of this project could also help the process of drinking water system. Since human has been contaminated by a lot of sickness and it is founded that alkaline water is good for human, therefore this project also could be use to control the alkalinity of water instead of neutralization.